2018
DOI: 10.1175/jpo-d-17-0169.1
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality in Transition Scale from Balanced to Unbalanced Motions in the World Ocean

Abstract: The transition scale Lt from balanced geostrophic motions to unbalanced wave motions, including near-inertial flows, internal tides, and inertia–gravity wave continuum, is explored using the output from a global 1/48° horizontal resolution Massachusetts Institute of Technology general circulation model (MITgcm) simulation. Defined as the wavelength with equal balanced and unbalanced motion kinetic energy (KE) spectral density, Lt is detected to be geographically highly inhomogeneous: it falls below 40 km in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

28
220
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 158 publications
(273 citation statements)
references
References 43 publications
(47 reference statements)
28
220
1
Order By: Relevance
“…Such slope discontinuity is not observed on the KE spectrum from surface motions (gray curve on Figure b). These results, similar to those reported in Rocha, Gille, et al () and Qiu et al (), are consistent with the ω ‐k spectra on Figures c and f, indicating that in summer, IGWs much more dominate the SSH field than the KE field for scales <50 km. Considering SSH as a proxy for potential energy (PE), this suggests these conspicuous differences between KE and SSH spectra in summer should be explained in terms of the relationship between PE and KE that differs for BMs and IGWs (as detailed in Gill, ; see also Qiu et al, ).…”
Section: Analysis Of the Frequency‐wave Number Spectra For The Differsupporting
confidence: 92%
See 4 more Smart Citations
“…Such slope discontinuity is not observed on the KE spectrum from surface motions (gray curve on Figure b). These results, similar to those reported in Rocha, Gille, et al () and Qiu et al (), are consistent with the ω ‐k spectra on Figures c and f, indicating that in summer, IGWs much more dominate the SSH field than the KE field for scales <50 km. Considering SSH as a proxy for potential energy (PE), this suggests these conspicuous differences between KE and SSH spectra in summer should be explained in terms of the relationship between PE and KE that differs for BMs and IGWs (as detailed in Gill, ; see also Qiu et al, ).…”
Section: Analysis Of the Frequency‐wave Number Spectra For The Differsupporting
confidence: 92%
“…These results, similar to those reported in Rocha, Gille, et al () and Qiu et al (), are consistent with the ω ‐k spectra on Figures c and f, indicating that in summer, IGWs much more dominate the SSH field than the KE field for scales <50 km. Considering SSH as a proxy for potential energy (PE), this suggests these conspicuous differences between KE and SSH spectra in summer should be explained in terms of the relationship between PE and KE that differs for BMs and IGWs (as detailed in Gill, ; see also Qiu et al, ). Indeed, using a shallow water model associated with a given vertical normal mode (in that case, PE is directly related to SSH), it can be shown that on one hand, the relationship between KE and PE for BMs in the spectral space (using the geostrophic approximation) is simply given by: trueKÊ=trueSSĤ2g2f2k2, …”
Section: Analysis Of the Frequency‐wave Number Spectra For The Differsupporting
confidence: 92%
See 3 more Smart Citations